PENGEMBANGAN VIRTUAL CLASS MATEMATIKA BERBASIS WEB MENGGUNAKAN MOODLE DAN WORDPRESS DI UNIVERSITAS MUHAMMADIYAH JEMBER - Rhomdani, Rohmad Wahid (Gammath : Jurnal Ilmiah Program Studi Pendidikan Matematika, 2016)
The rapid information and communication technology nowadays requires education to contribute in developing instructional media. One of the rapid information and communication technology in education is a Course Management System (CMS) and Content Management System (CMS) which is designed to facilitate the Lecturer in managing long distance learning (online). One of CMS application that quite popular is Wordpress and Moodle. Moodle is a software package that is useful for creating and conducting courses / training / education-based internet. Moodle given away for free as open source software (licensed under the GNU Public License). It means, despite it has the copyright, Moodle still be given the freedom to copy, use, and modified. Moodle can be obtained at the address http://moodle.org/download. Moodle is an acronym for Modular Object Oriented Dynamic Learning Environment. Moodle has a module that can create quizzes. Wordpress is one of Content Management System (CMS) that is Open Source, is free software that can be used to make the web the simplest to the most complex, such as a web portal. Called open source because the user can modify, delete, or add a script that is included in the software as long as include the copyright remain origins and obey the rules that have been agreed together. Merging the two CMS Wordpress and Moodle CMS made to produce a dynamic virtual class, interactive and practical. Therefore, the developing researchers of digital learning management system (LMSD) used Worple as a mathematics virtual class in UNMUH Jember. Finally, this research is to produce a dynamic website, interactive and practical to develop digital learning management system in UNMUH Jember. The method used in this research is the kind of research and development according to Gall and Brog (type Expositori research product development), with the data collection methods of literature studies, interviews, and questionnaires. This research included respondents from students, lecturers, and designer. Keywords: Virtual Class, Moodle end Wordpress